(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
During the years of independence, cultural and educational events became one of the important issues at the center of the state’s attention. The scope of events aimed at fostering the spiritual and moral development of students was expanded. The issue of spirituality was viewed as a force that purifies a person spiritually, strengthens their inner world, willpower, and solidifies their faith and beliefs.